2011
DOI: 10.3945/jn.110.131318
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Zinc Deficiency Reduces Testicular Zip6 and Zip10 Abundance and Impairs Spermatogenesis in Mice

Abstract: Male infertility accounts for ~40% of cases of failure to conceive. Testes have a strict zinc (Zn) requirement and severe Zn deficiency compromises spermatogenesis, sperm viability, and motility, compromising fertility in men. Despite the high prevalence of marginal Zn deficiency in humans, less emphasis has been placed on understanding the consequences on male reproduction. Swiss Webster mice were used to visualize Zip protein expression during spermatogenesis using immunohistochemistry. Data suggest Zip5 imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
70
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 40 publications
4
70
1
2
Order By: Relevance
“…Zinc (Zn) influences the functioning of the male reproductive system, is involved in steroidogenesis, promotes the maturation of sperm and, as an inhibitor of 5-a-reductase, regulates the concentration of dihydrotestosterone formed from testosterone. Zn excess contributes to the growth of the prostate gland (Croxford et al 2011;Fahim et al 1993), while a deficiency may cause hypogonadism, decreased testosterone levels, impaired fertility and reduced sperm viability and quantity (Yamaguchi et al 2009;Prasad 2008). In men, disruption of the Zn-to-Cu ratio reduces libido and results in erectile dysfunction and prostatic hyperplasia.…”
Section: Introductionmentioning
confidence: 98%
“…Zinc (Zn) influences the functioning of the male reproductive system, is involved in steroidogenesis, promotes the maturation of sperm and, as an inhibitor of 5-a-reductase, regulates the concentration of dihydrotestosterone formed from testosterone. Zn excess contributes to the growth of the prostate gland (Croxford et al 2011;Fahim et al 1993), while a deficiency may cause hypogonadism, decreased testosterone levels, impaired fertility and reduced sperm viability and quantity (Yamaguchi et al 2009;Prasad 2008). In men, disruption of the Zn-to-Cu ratio reduces libido and results in erectile dysfunction and prostatic hyperplasia.…”
Section: Introductionmentioning
confidence: 98%
“…In males, zinc deficiency leads to poor semen quality, impaired sperm motility, abnormal head morphology, and reduced number of viable sperm (25)(26)(27). In females, dietary zinc deficiency causes developmental problems throughout pregnancy (28 -30).…”
mentioning
confidence: 99%
“…Studies in animal models as well as clinical studies have demonstrated that hypogonadism is a prominent feature of Zn deficiency in humans and animals (37,38); however, the underlying mechanisms responsible for these endocrine effects observed in Zn deficiency remain unclear. The present study has reported a significant decrease in serum testosterone levels and Zn concentrations in the testis and Leydig cells of mice, which is in line with the findings of previous studies on a number of male mammal species (37)(38)(39)(40). In addition, ZnT7 was prinicipally expressed and colocalized with StAR in the Leydig cells of male CD-1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that ZnTs are involved in a number of physiological pathways and processes, such as insulin synthesis and secretion in the pancreas, cognitive function, bone development and body adiposity (37,45). The roles of ZnTs in the pathogenesis of disease have received great attention and monitoring cellular Zn status may have an important impact on disease prevention and treatment (45,46).…”
Section: Discussionmentioning
confidence: 99%